SPASIAL PERUBAHAN TUTUPAN LAHAN MENGGUNAKAN METODE SUPERVISED CLASSIFICATION PASCA BENCANA BANJIR BANDANG DI KECAMATAN PAUH, DAS BATANG KURANJI - Adhelia Josi Wulan Sari; Helfia Edial (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Land cover change is an important indicator for describing the dynamics of the Earth's surface, particularly following disaster events. Information on post-flash flood land cover change and its spatial distribution patterns in Pauh District within the Batang Kuranji Watershed remains limited, highlighting the need for analyses capable of identifying both the magnitude of land cover change and its spatial characteristics. This study aimed to: (1) analyze land cover conditions before and after the flash flood event; (2) examine post-disaster land cover change; and (3) analyze the spatial distribution pattern of land cover change in Pauh District within the Batang Kuranji Watershed. A descriptive quantitative approach was employed using spatial analysis based on Remote Sensing and Geographic Information Systems (GIS). Land cover classification was performed using the Supervised Classification method with the Maximum Likelihood Classification (MLC) algorithm on Sentinel-2A imagery acquired in 2025 and January 2026, and the classification results were validated using a Confusion Matrix. Land cover change was analyzed using the Post-Classification Comparison (PCC) method through overlay techniques, while the spatial distribution pattern was examined using the Average Nearest Neighbor (ANN) method. The results indicate that the vegetation class remained the dominant land cover, covering 11,416 ha (95.64%) in 2025 and 11,004 ha (92.19%) in 2026. The classification achieved high accuracy, with an Overall Accuracy of 97.67% and a Kappa Coefficient of 0.965. Land cover change occurred over 443 ha (3.71%) of the study area, with the largest transition being from vegetation to bare land, covering 329 ha. The most extensive land cover change was identified in Lambung Bukit Village. The ANN analysis produced a Nearest Neighbor Ratio (NNR) of 0.42, indicating that the spatial distribution of land cover change exhibited a clustered pattern. These findings demonstrate that post-flash flood land cover change was concentrated along the Batang Kuranji River corridor and the upstream watershed area, providing valuable spatial information to support environmental monitoring and post-disaster land management